Seeking surrogates for taxonomic and functional evaluations of leaf-litter ant faunas. (March 2021) - Koch, Elmo B.A.; Nascimento, Ivan Cardoso; Majer, Jonathan D.; Delabie, Jacques H.C.
Highlights: Biodiversity surrogates provide meaningful information at a lower cost and effort. Ants are often used in such environmental assessments. We seek a useable substitute surrogate for taxonomic and functional ant diversity. For this, we tested four potential ant surrogates at 65 Atlantic rainforest sites. Of the species and functional group surrogates, mixed-level was the best. Abstract: Comprehensive biodiversity inventories are expensive and time-consuming to achieve, especially for groups of megadiverse organisms. One approach to resolve such situations is to utilize biological substitutes, referred to as surrogates. A surrogate should provide meaningful information at a lower cost and/or effort than the original level of resolution. Studies have shown that species richness is often not the best or most appropriate component or predictor of biodiversity. Functional diversity can be used as a measurement of the ecological differentiation between habitats or between biological functions. We evaluated the use of several taxonomic metrics as potential surrogates for leaf-litter ant assemblages distributed in 65 Atlantic rainforest sites. Our goal was to find reliable and economic substitutes for both taxonomic and functional leaf-litter ant diversity and composition. We tested four potential surrogate approaches for taxonomic metrics and three for functional group metrics. Additionally, we also evaluated the time and costs involved. We used a large leaf-litter ant database that comprises 364 ant species, respectively classified into 13 or 26 ant functional groups based on either a general and specific resolution. Subfamily was found to be an unacceptable surrogate for both taxonomic and functional group metrics. Mixed-level and indicator taxa metrics were rated as 'excellent' taxonomic surrogates. Mixed-level and genus metrics were rated as 'excellent' or 'acceptable' functional group surrogates when considering the most general functional resolution, while mixed-level and genus were considered as 'excellent' surrogates when considering the more specific resolution. The monetary and time costs to identify ants to genus level were lower than those using indicator taxa and mixed-level metrics. The use of a certain higher taxon functional and taxonomic surrogates allows a reduction of survey and analysis costs while still enabling the analysis of biological diversity from the taxonomic and functional point of view.